Mental health for primary care professionals : The role and leadership of management and health systems in mental health promotion in working settings - Cipta, Darien Alfa; Reina, Natasya; William, Dyta Ghezhanny; Mendive, Juan; Rogers, Heather L.; Petrazzuoli, Ferdinando ; 0000-0003-1058-492X (Challenges in Primary Mental Health Care : Models for Interdisciplinary Collaboration, 2025)
The mental health of the health workforce has been receiving more attention, especially since the pandemic. Levels of burnout, moral injury, and mental disorders, including suicide, among physicians are cause for concern. Healthcare leadership in workplaces plays a crucial role in addressing this important issue, which is also related to the ability to attract and retain physicians. This chapter provides an overview of mental well-being and a framework to understand groups of associated factors. Burnout and moral injury are examined, and the importance of emotional resilience is explored. The following section reviews multi-level interventions that can be implemented to improve the mental well-being of physicians at work. First, there is a distinction between interventions that modify the individual, modifying internal factors that influence well-being, and those that aim to influence the environment of the person. Interventions that modify the external factors around the physician can be divided into organizational-level and community-level interventions. Ultimately, comprehensive interventions at all levels addressing individual, organizational, and community factors are recommended. Case studies are described that offer examples of best practices to improve physician well-being. Since performance metrics provide indicators of what an organization values, a metric that is not commonly used to measure organization performance, specifically the compassion aspect of the institution, is proposed to ensure psychologically safe workplaces. Leadership and multidisciplinary teamwork are key to institutionalized compassion in daily clinical practice and running the business of healthcare organizations.